2014
DOI: 10.11648/j.avs.20140204.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bovine Tuberculosis and Its Risk Factors in Cattle and Humans, at and around Dilla Town, Southern Ethiopia

Abstract: A cross-sectional study was carried out from February, 2012 to June, 2013 using comparative intradermal tuberculin (CIDT) test on 440 individual live cattle kept in 118 housholds/farms to determine the prevalence of, and to identify the risk factors associated with, bovine tuberculosis (BTB) infection in cattle and to assess the public awareness on its zoonotic importance through structured questionnaires at and around Dilla town, southern Ethiopia. The herd and individual cattle prevalence of bovine tuberculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 21 publications
7
21
3
Order By: Relevance
“…Respondents’ awareness on BTB was generally poor (34.3%, 24/70), and magnifies the public health implication of the disease in the study area. Our finding is consistent with 35, 25.7, 6.9, 29.7 and 15% awareness levels reported in earlier Ethiopian studies [12, 13, 17, 27, 28]. The low level of awareness observed in the present study could also be related to the low level of BTB in the study area.…”
Section: Discussionsupporting
confidence: 92%
“…Respondents’ awareness on BTB was generally poor (34.3%, 24/70), and magnifies the public health implication of the disease in the study area. Our finding is consistent with 35, 25.7, 6.9, 29.7 and 15% awareness levels reported in earlier Ethiopian studies [12, 13, 17, 27, 28]. The low level of awareness observed in the present study could also be related to the low level of BTB in the study area.…”
Section: Discussionsupporting
confidence: 92%
“…But it is higher than the reports of Mamo et al (2009) at Dire Dawa, and Gumi et al (2011) in Southern Ethiopia. Similarly, it is significantly higher than previously reported prevalence of some other authors at different sites in Ethiopia (Gumi et al, 2011(Gumi et al, , 2012Tamiru et al, 2013;Admasu et al, 2014;Ameni and Aklilu, 2007;Romha et al, 2014;Nuru et al, 2015), in Zambia (Pandey et al, 2013), in Ecuador (Proano-Perez et al, 2009) in Bangladesh (Mondal et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…However, prevalence of 13.93% for Borena and 32.81% for Metehara origin camels at a cut off value ≥ 2mm was observed and this was statistically significant (χ 2 = 13.46, P= 0.000). Some other recent studies reported strong association between breed type and tuberculin positive reactivity for cattle in different sites at a cut off value ≥ 4mm (Admasu et al, 2014;Romha et al, 2014;Zeru et al, 2014;Nuru et al, 2015). This prevalence report was significantly higher for Metehara camels than Borena camels.…”
Section: Discussionmentioning
confidence: 77%
“…This result was in agreement with a study conducted in Addis Ababa that reported 99.5% [14] and in southern Ethiopia 99.6% [15], who found a profound awareness on human TB among high school students. Nevertheless, [21] indicated a lower (29.7%) awareness on TB occurrence in animals among cattle owners in the southern part of Ethiopia. Likewise, [22] reported that 69.0% of respondents have no information about bTB among the community in the Gambella region, southwest Ethiopia.…”
Section: Discussionmentioning
confidence: 93%
“…In line with this, [14] reported similar results among high school students in Addis Ababa. Likewise, [31] and [21] highlighted that only 22.9% and 16.6% of respondents believed the fact that TB can be acquired from animals, respectively. Apart from the variation due to the study population's differences in multicultural practice in the respective study areas, it also implicates the wide knowledge gap among the general community regardless of age group.…”
Section: Discussionmentioning
confidence: 99%